Breaking bad news with CONSOLE: Toward a framework integrating medical protocols with crisis communication - TAN, Kevin Kok-Yew (Institutional Knowledge at Singapore Management University, 2019)
This paper develops the CONSOLE (Coherence, Orientation, Nuance, Support, Ongoing, Leadership, Emotions) framework to guide practitioners on how to break bad news effectively to stakeholders during crises. Arguably the first study integrating well-established medical protocols such as SPIKES (Baile et al., 2000) and COMFORT (Villagran et al., 2010) with crisis communication literature, the CONSOLE framework is applied on four aviation crises to examine the manner in which organizations communicate bad news on social media platforms, which are increasingly used to communicate with stakeholders (Siah, Bansal & Pang, 2010). Data was obtained during the height of the crises (Vasterman, 2005) from official Twitter and Facebook pages of Malaysia Airlines, AirAsia and Asiana Airlines. Findings showed that the airlines’ communication of bad news to stakeholders suffer from emotional deficit. Practitioners can use the CONSOLE framework to break bad news in a holistic and empathetic manner during crises.